Porphyrin-based conjugated microporous polymers with dual active sites as anode materials for lithium-organic batteries. (5th March 2022) - Shu, Lilei; Yu, Jie; Cui, Yuan; Ma, Yuqin; Li, Yanhui; Gao, Bo; Wang, Heng-guo
Abstract: Conjugated microporous polymers have been regarded as ideal electrode materials for green lithium-ion batteries (LIBs) considering their advantages such as insolubility, adjustable structure and porosity. Herein, we synthesize porphyrin-based CMPs (Co-PCMPs) with dual active sites composed of metal-N4 conjugated macrocycle and conjugated carbonyl groups through the condensation polymerization. In view of the rational design and unique organic skeleton, when used as the anode material for LIBs, Co-PCMPs show a high capacity (700 mAh g −1 at 0.05 A g −1 ) and excellent rate capability (400 mAh g −1 at 1.0 A g −1 ). Meanwhile, theoretical calculations are used to further study the lithium storage mechanism of Co-PCMPs as the anode material for LIBs. In addition, a full cell is also assembled by using LiCoO2 as the cathode material and Co-PCMPs as the anode material, which also shows a high capacity (212 mAh g −1 at 0.05 A g −1 ) and good rate capability (116 mAh g −1 at 0.2 A g −1 ), implying the possibility of practical applications of this type of conjugated microporous polymers. Graphical abstract: We synthesize porphyrin-based conjugated microporous polymers with dual active sites composed of metal-N4 conjugated macrocycle and conjugated carbonyl groups through the condensation polymerization, which could be served as anode materials to a full cell of lithium ion batteries. Image 1 Highlights: Porphyrin-based conjugated microporous polymers were prepared by condensation reaction. The polymers with dual active sites were used as anode materials for lithium ion batteries. Full cell is also assembled to show the possibility of practical applications of these polymers.